IEEE International Conference on Communications, 2003. ICC '03.
DOI: 10.1109/icc.2003.1204547
|View full text |Cite
|
Sign up to set email alerts
|

New results on the capacity of M-ary PPM ultra-wideband systems

Abstract: Abstract-In this paper, some new results on the capacity of a typical M -ary pulse position modulation (M -PPM) time hopping (TH) Ultra-Wideband (UWB) system are presented. Previous results using a "pure PPM model" are proven to exaggerate the real capacity of a UWB system. Based on an extended model containing correlator and soft decision decoding, the capacity is evaluated in the single-user case and in the case of a system with asynchronous multiple user interference (MUI) when the inputs are equiprobable. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The obtained capacity expressions are independent of the shape of the used pulse. However, the results based on this pure PPM model actually exaggerate the capacity of a UWB system as shown in [11]. To bound the capacity more tightly, new models should be constructed to reflect all critical components of a UWB system.…”
Section: A Uwb Capacity In Awgn Channelsmentioning
confidence: 99%
“…The obtained capacity expressions are independent of the shape of the used pulse. However, the results based on this pure PPM model actually exaggerate the capacity of a UWB system as shown in [11]. To bound the capacity more tightly, new models should be constructed to reflect all critical components of a UWB system.…”
Section: A Uwb Capacity In Awgn Channelsmentioning
confidence: 99%
“…So OPPM is not applicable to TH-UWB without further design considerations. For overlapped PPM, the optimal modulation parameter is smaller than the width of a pulse because the values of the pulse's autocorrelation could be negative [14]. The other modulation methods cause little time jitter.…”
Section: Conditions For Clean Rake Outputmentioning
confidence: 99%
“…The mean SEP can be evaluated numerically via Monte Carlo simulation with (14). An alternative way can be used to arrive at an explicit expression, considered next.…”
Section: Derivation Of Explicit Expressions Of Performancementioning
confidence: 99%
“…The maximum value of (9) is achieved when the system has equally likely input symbols in the binary modulation scheme [10], [19]. Therefore, the channel capacity for the desired user can be calculated as…”
Section: A Awgn Channelmentioning
confidence: 99%
“…For the same system, authors in [9] showed that the channel capacity is highly affected by pulse shapes. By modeling the multiple access interference (MAI) as Gaussian, the analysis on the channel capacity was extended to AWGN channels with multiple users in [10] - [13]. In [14], the channel capacities of pulse amplitude modulation (PAM) and PPM were compared over AWGN channels, where the MAI was also modeled as Gaussian.…”
Section: Introductionmentioning
confidence: 99%